Retos y perspectivas de la gobernanza del agua y gestión integral de recursos hídricos en Bolivia - Ruiz, Sergio Antonio; Gentes, Ingo Georg (European Review of Latin American and Caribbean Studies, 2008)
Abstract: Challenges and perspectives of water governance and integrated water resource management in BoliviaBolivia is not only highly affected by social and political instability, but also by erosion and climate change and an indiscriminate and vast exploitation of its natural resources. The new policy structure seeks to establish a broad consensus on better water governance relying on a participatory democracy approach and the commitment to indicators for sustainable development. The creation of a Water Ministry in 2006, which emerged from the water riots against privatization of water rights and sanitation services in 2000, can be interpreted as a clear sign for more integration of social movements and civil organizations. But at the present these organizations seemed to be marginalized from the decision-making process, and government and public institutions are confronting a complex situation of weakened legitimacy. The present paper offers an insight on the ongoing process, including the challenges and obstacles for the implementation of a new water policy and local integrated water management systems. The reflections consider the official legal framework and a policy analysis in order to illustrate the conflictive schemes in different regions and localities. The final aim is to indicate the gaps between the official discourse and local realities for water governance and to indicate some recommendations for a more coherent public-civic action in water governance, control and transparency. Resumen:Bolivia no solo es afectada por una inestabilidad social y política, sino también por erosión, efectos del cambio climático y una explotación indiscriminada de los recursos naturales. La nueva política de cambio social se propone, entre otros objetivos, lograr un consenso amplio de gobernanza en el agua, basado en un proceso democrático participativo y el compromiso de cumplir indicadores de desarrollo sostenible. La creación del nuevo Ministerio del Agua en el año 2006, que surgió de movimientos sociales como la ‘guerra por el agua’ en Cochabamba en el 2000, abrió una nueva perspectiva para las políticas hídricas en Bolivia. No obstante, a dos años de gestión, la nueva política hídrica boliviana se encuentra estancada, entre otros motivos, debido al debilitamiento político y técnico del propio Ministerio del Agua, que no permite coordinar acciones con las instancias públicas de los gobiernos departamentales y municipales, y la escasa coherencia entre las normas que regulan las actividades del sector. El presente documento expone los retos y las perspectivas del proceso de formulación e implementación de la política nacional de agua en Bolivia, sobre la base de reflexiones respecto del marco regulatorio existente y la estrategia de implementación sectorial de riego, agua potable y cuencas. El objetivo final es delinear las brechas entre el discurso oficial en el agua y las realidades y dificultades locales y regionales en el agua e indicar algunos métodos alternativos para una acción cívico- pública más coherente en la gobernanza del agua y la gestión integrada de recursos hídricos.